1979
DOI: 10.1007/bf00538942
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of growth hormone response to insulin, arginine and haemodialysis in uraemic children

Abstract: Plasma growth hormone (GH) concentrations after insulin and arginine stimulation were estimated in 11 dialyzed and 6 non-dialyzed children with chronic renal failure. Twenty healthy children served as controls. Plasma GH peak concentration and estimation of the total area under the plasma GH concentration-time curve by the trapezoidal rule were used to evaluate results. Elevated basal GH levels and an exaggerated response to the stimuli were seen in several of the patients. The causes of the abnormal GH secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The effect of various aminoacids upon the release of GH and PRL has been studied in man. Intravenous administration of arginine in pharmacological doses stimulates the release of GH (Knopf et al 1965;Merimee et al 1965;Friesen et al 1972;BratuschMarrain and Waldh~iusl 1979;Ijaiya 1979) and PRL Guyda and Friesen 1973;Rakoffet al 1973;Onishi et al 1976;Bratusch-Marrain and Waldh~iusl 1979) but release of PRL after arginine infusion is believed to occur only in a small percentage of the subjects studied. In the present study, the time courses of GH and PRL release were dissociated and occurred approximately 15min earlier for PRL than GH.…”
Section: Discussionmentioning
confidence: 95%
“…The effect of various aminoacids upon the release of GH and PRL has been studied in man. Intravenous administration of arginine in pharmacological doses stimulates the release of GH (Knopf et al 1965;Merimee et al 1965;Friesen et al 1972;BratuschMarrain and Waldh~iusl 1979;Ijaiya 1979) and PRL Guyda and Friesen 1973;Rakoffet al 1973;Onishi et al 1976;Bratusch-Marrain and Waldh~iusl 1979) but release of PRL after arginine infusion is believed to occur only in a small percentage of the subjects studied. In the present study, the time courses of GH and PRL release were dissociated and occurred approximately 15min earlier for PRL than GH.…”
Section: Discussionmentioning
confidence: 95%
“…Circulating growth hormone (GH) concentrations are either elevated or at the upper limit of normal in chronic renal failure (uraemic) patients (Saaman & Freeman, 1970;Czernichow et al, 1976). Furthermore, inappropriate or exaggerated GH responses to a whole range of stimuli have been reported (Gonzalez-Barcena et al, 1973;Wright et al, 1968;Orskov & Christensen, 1971;Ijaiya, 1979;Marumo et al, 1979). As the kidney catabolizes GH (Johnson & Maack, 1979;Rabkin et al, 1972), the abnormally elevated basal values and responses to stimuli have been attributed to the reduced clearance of G H in uraemia (Salmon et al, 1962;Bessarione et al, 1987).…”
mentioning
confidence: 99%
“…Inadequate nutrition may play a role, but there were hints that low somatomedin C (IGF-1) activity could also be an important contributing factor ( 68 , 69 ). By the end of the decade children were undergoing GH stimulation tests that suggested that GH deficiency was likely not the cause of their slow growth, but rather GH resistance may be the underlying factor ( 70 ). Could “flooding the system” with rhGH be the answer to permitting children with CRI to grow more quickly?…”
Section: Chronic Renal Insufficiency (1993)mentioning
confidence: 99%